Literature Review: Global Competencies and World-Class University Outcomes in Indonesia - Teguh Triwiyanto; Desi Eri Kusumaningrum; Pramono Pramono; Muh. Arafik; Ahmad Nurabadi; Baidhowi Muslikh (International Research-Based Education Journal, 2024)
This literature review research aims to synthesize the global competencies and outcomes of world-class universities in Indonesia. In conducting the literature review on global competence and world-class university outcomes in Indonesia, the researcher used a careful approach that included several steps. First, a precise research problem was formulated, sharpening the intersection between global competencies and the performance of world-class universities in Indonesia. After the collection of relevant literature, the researcher critically evaluated the collected data in terms of its contribution to the overarching research question. Through careful analysis and interpretation, the researcher synthesized the findings, identifying patterns, differences, and areas that warrant further investigation.  The data collected was based on searches in Publish or Perish - Harzing in 2024 according to search engine guidelines from library professionals and a trial of words and combinations for different possibilities and percentages of relevant research articles on selected criteria. The results show that achieving world-class university status in Indonesia is strongly related to the development and improvement of global competencies in higher education institutions. Transformation driven by globalization requires students, lecturers and administrators to be equipped with the skills to thrive in a global academic environment.